DI-040 Long-term effect of an individualised medication plan with drug administration recommendations on the patients' drug knowledge. (24th March 2015) - Send, AFJ; Haefeli, WE; Seidling, HM
Abstract : Background: Inadequate patient knowledge of their drugs correlates with medication errors. An enhanced medication plan with recommendations about drug administration increased patients' drug knowledge at hospital discharge by 64% [Send et al . 2014]. However, because behavioural changes may soon be lost, the benefits of such patient education measures may be only short-term. Purpose: To assess the long-term effect of a medication plan with recommendations about drug administration in a prospective randomised controlled study in an outpatient setting. Material and methods: The study was conducted in four family practices with patients using five or more drugs. After inclusion, the patients' current knowledge of their drugs was assessed using three standardised questions about their pharmacotherapy. Thereafter, patients were randomised to receive a medication plan either containing only standard information (i.e. drug name, active ingredient name, strength, drug regimen, dosage form; control group) or enhanced with drug administration recommendations and indications (intervention group). After approximately two months, patients were contacted again and their drug knowledge was reassessed. Results: Of the 120 patients enrolled (60 per group), 42 patients in the control group (8.4 ± 3.3 drugs) and 45 in the intervention group (7.4 ± 2.8 drugs; p = 0.12) completed the study. Drug knowledge was similar in both groups at the beginning of the study (43.7% vs. 40.7% correct answers; p = 0.63). After 2 months, patient drug knowledge had increased in the intervention group compared to the control group (65.2% vs. 46.0% p = 0.002) with 14 patients in the intervention group answering all three questions correctly compared to only 4 patients in the control group (p = 0.012). Conclusion: Positive long-term effects of patient education in the form of an active intervention are possible. A personalised medication plan enhanced with drug administration recommendations persistently increased the drug knowledge of patients with polypharmacy. References and/or acknowledgements: No conflict of interest.